Effect of electrophilic substitution and destructive quantum interference on the thermoelectric performance in molecular devices. (7th June 2019) - Cao, Xuan-Hao; Wu, Dan; Feng, Ye-Xin; Zhou, Wu-Xing; Tang, Li-Ming; Chen, Ke-Qiu
Abstract: Using density function theory combined with the non-equilibrium Green's function method, the thermoelectric properties of para-Xylene-based molecular devices are investigated. It is found that destructive quantum interference can be triggered in n-type of para-connected para-Xylene-based molecular device and can obviously enhance the thermoelectric performance of the devices. Moreover, bridge atom electrophilic substitution can significantly improve the thermoelectric properties of p-type monolayer molecular device. The ZT value of p-type monolayer molecular device with doped electrodes can be optimized to 2.2 at 300 K and 2.8 at 500 K, and n-type bilayer molecular device can achieve the value of 1.2 at 300 K and 2.0 at 500 K. These results offer the information to design the complete molecular thermoelectric device with p-type and n-type of components and to promote the thermoelectric properties of bilayer molecular junctions by employing destructive quantum interference effects.